Air Potato Leaf Beetle (Suggested Common Name), Lilioceris cheni Gressitt and Kimoto (Insecta: Coleoptera: Chrysomelidae: Criocerinae) - Rodrigo Diaz; William A. Overholt; Ken Hibbard (EDIS)
This leaf feeding beetle was recently introduced into Florida from China for biological control of air potato. This 4-page fact sheet provides information on the distribution, appearance, life cycle, host range and importance of the beetle. Written by Rodrigo Diaz, William A. Overholt, and Ken Hibbard, and published by the UF Department of Entomology and Nematology, January 2013.